An Introduction to Technical Theatre - Sanders, Tal (Open textbook library., 2018)
An Introduction to Technical Theatre draws on the author’s experience in both the theatre and the classroom over the last 30 years. Intended as a resource for both secondary and post-secondary theatre courses, this text provides a comprehensive overview of technical theatre, including terminology and general practices. Introduction to Technical Theatre’s accessible format is ideal for students at all levels, including those studying technical theatre as an elective part of their education. The text’s modular format is also intended to assist teachers approach the subject at their own pace and structure, a necessity for those who may regularly rearrange their syllabi around productions and space scheduling.